Inspectors and Auditors: Some Sources of Andrey Platonov’s Work of the 1920s - Maria V. Osipenko (Studia Litterarum)
The article examines the work of Andrey Platonov of the 1920s in the context of the history of the Soviet state and Communist Party administration departments. Allusions to the activity of these authorities are present in many of Platonov’s works (“Gorod Gradov,” “Administrativnoe Estestvoznanie,” “Usomnivshiysya Makar,” “Nadlezhachie Meropriyatiya (Socialnaya Satira nashih dney),” etc.). Most of the references relate to anti-bureaucratic and rationalization activities of these power and control authorities. The effort to perfect bureaucratic machine is represented in Platonov’s work as pseudoproductive, pseudo-scientific, and meaningless activity. Yet, it is also shown how such pseudo-organization can become real life-threatening force.